(untitled) (2013)
Currently, software acquisition is strategic for organizations. Companies need support to succeed in software acquisition projects because such projects commonly present high failure rates. To solve this problem, it is necessary to design mechanisms for software acquisition, such as risk classification to identify the typical risks that may affect the success of a software acquisition project. Thus, herein, we present a case study, showing the implementation of a risk taxonomy whose structure is designed using a method for its construction, with a mechanism to reduce the risk of acquisition projects that adversely affect their success. © 2013 World Scientific Publishing Company.